2020
DOI: 10.1186/s12889-020-08999-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of hearing loss and posttraumatic stress disorder among injured military personnel: a retrospective study

Abstract: Background: Posttraumatic stress disorder (PTSD) and hearing loss are hallmark public health issues related to military service in Iraq and Afghanistan. Although both are significant individual contributors to disability among veterans, their co-occurrence has not been specifically explored. Methods: A total of 1179 male U.S. military personnel who sustained an injury between 2004 and 2012 during operations in Iraq or Afghanistan were identified from clinical records. Pre-and postinjury audiometric data were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…It may be that because of the treatable nature of hearing problems, as opposed to the difficulties associated with treating tinnitus, hearing problems are less of a persistent reminder of traumatic events [44]. In contrast to the present findings, a recent study in the US Armed Forces found that hearing loss was associated with a greater burden of PTSD [45]. However, the US study only examined people who sustained hearing loss through injuries during the Iraq or Afghanistan conflicts, suggesting that the cause of auditory problems may affect these associations.…”
Section: Associations Between Auditory Problems and Mental Health Problems And Alcohol Misusecontrasting
confidence: 99%
“…It may be that because of the treatable nature of hearing problems, as opposed to the difficulties associated with treating tinnitus, hearing problems are less of a persistent reminder of traumatic events [44]. In contrast to the present findings, a recent study in the US Armed Forces found that hearing loss was associated with a greater burden of PTSD [45]. However, the US study only examined people who sustained hearing loss through injuries during the Iraq or Afghanistan conflicts, suggesting that the cause of auditory problems may affect these associations.…”
Section: Associations Between Auditory Problems and Mental Health Problems And Alcohol Misusecontrasting
confidence: 99%
“…Substance use disorders, including alcohol use disorder, are prevalent among veterans of recent conflicts and have been associated with up to four times the odds of PTSD and depression (Seal et al., 2011). Opioid abuse (Beyer et al., 2019), chronic pain (Cifu et al., 2013; Higgins et al., 2014; Lee et al., 2019), low‐back pain (Watrous et al., 2020), headache (Jaramillo et al., 2016), and hearing loss (MacGregor et al., 2020) have also been associated with increased likelihood of mental health diagnoses among injured service members. Additionally, injured service members who report poorer sleep and more tobacco use are more likely to screen positive for mental health outcomes (McCabe et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly acknowledged that industrial workers and individuals in military service have inevitably faced more noise exposure and that exposure has increased the incidence of noise-induced hearing loss (NIHL) [ 1 , 2 ]. Not only temporary noise exposure of high intensity (i.e., more than 85 dBA) in terms of level of intensity, but also continuous exposure to moderate-intensity noise in terms of frequency can contribute seriously to negative effects on the human auditory system [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%